Women workers and the politics of claims-making in a globalizing economy - Naila Kabeer (United Nations Research Institute for Social Development (UNRISD), 2015)
The paper analyses the evolving politics of claims-making by women workers in the Global South in the context of a globalized economy. It addresses the following questions. What kinds of claims are prioritized in relation to women workers? Who is making these claims? To whom are they addressed? What strategies are pursued to advance these claims? Which claims are heard and acted on - and which go unheard? The paper considers three categories of women workers: those working in global value chains, those working for domestic markets and those working as cross-border migrants. It also distinguishes between claims made by, with and on behalf of women workers. The analytical framework weaves ideas on the politics of gender-equality claims-making with work on the politics of recognition, redistribution and representation and analysis of the strategies deployed by transnational networks. Claims relating to workers in global value chains have been largely made on their behalf by anti-sweatshop campaigns led by Northern-based organizations, including trade unions, church groups, student activists and concerned consumers. The claims are largely addressed to the transnational corporations that drive these value chains, although their demands may include pressure on the states in which these corporations are headquartered. Claims relating to women working for domestic markets, primarily in the informal economy, tend to be made by organizations of women workers themselves, often with the support of locally based NGOs. The claims are largely addressed to the state, although as these organizations come together in international networks, they have also begun to pitch their claims to institutions of global governance, particularly the International Labour Organization (ILO) as well as international trade unions. Claims relating to migrant women workers tend to be made by locally based NGOs, sometimes made up of migrant workers themselves, in both sending and receiving countries. While the claims are largely addressed to the governments of these countries, they have also been picked by the emerging international networks of migrant workers and pitched to international institutions. The right to organize and to engage in collective bargaining is one of the most controversial rights when it comes to workers, particularly in global value chains. The assertion of this right frequently causes capital to cut and run in search of a cheaper and more docile labour force, and in turn, the fear of losing capital makes it harder for states to side with workers. States appear more responsive to some of the claims advanced by domestic workers organizations, but here too they appear to be more responsive to some claims (the extension of social protection to marginalized groups) than others (eliminating exploitative practices at work). The paper highlights the importance of "framing" within the strategies drawn on to make claims by, with and on behalf of women workers, because beyond the resources they are able to mobilize, the ability to put claims in compelling narratives determines their effectiveness in mobilizing wider support and resonating with those who have the power to act on those claims. It also argues that the construction and consolidation of associational power has to be factored in as a strategy in itself, particularly when it comes to women workers in the informal economy who are largely overlooked by the trade union movement. Women workers have organized in a variety of different forms, including trade unions, associations and cooperatives. Those supporting their claims have at times opted to work alongside the trade union movement and at others set up independent womens organizations. But given the patriarchal culture that persists in many mainstream unions, the paper argues that an autonomous organizational space is critical for women workers. It would allow them to develop an "oppositional consciousness" that challenges inequalities that have been taken for granted in their lives, to identify their own priorities and to craft alternative strategies for making claims that are better suited to their distinctive experiences and constraints. Given the globalized terrain within which the politics of claims-making is now playing out, there is an urgent need to develop conceptual tools to understand labour activism that is no longer confined to national boundaries.
Keywords: 330